Indikator Simple Moving Average dan Relative Strenght Index untuk Menentukan sinyal Beli dan Jual Saham pada Sektor Infrastruktur - Dina Yeni Martia; Nur Indriana Yasmine (The Indonesia Capital Market Institute, 2021)
Technical analysis is a methodology of forecasting stock price fluctuations whose data is taken from stock trading data that occur on the stock market (stock exchange). The indicator is used to support technical analysis, the indicator also serves as a tool to determine trends and buy and sell signals in a stock. This study aims to determine the difference between sell and buy signals suggested by the Simple Moving Average and Relative Strength Index indicators. The research method used is descriptive qualitative. The population in this study are publicly traded companies in the infrastructure sector on the Indonesia Stock Exchange. The results showed that in the analysis of the five stocks of ASSA, SAFE, TKLM, KOPI and TOWR using Simple Moving Averange (SMA) and Relative Strength Index (RSI) indicators showed quite accurate signals. Where the Simple Moving Average (SMA) Indicator is used to determine the direction of a stock's trend movement and the Relative Strength Index (RSI) indicator supports confirming the position and price level of a stock.